Solving the puzzle of strong French coffee, palpitation and dizziness. (14th February 2013) - Park, John Jungpa; Grubb, Neil
Abstract : A 38-year-old gentleman presented to the emergency department at the University Hospital in Geneva with nausea, rapid palpitation and presyncope. This was followed by a poor night's sleep, a day of strenuous walking in the city and drinking a large quantity of strong French coffee. 12-lead ECG revealed tachycardia with slightly increased QRS duration of right bundle branch block pattern and left axis deviation. Without the electrophysiological (EP) study, the patient was diagnosed with supraventricular tachycardia. On return to Edinburgh, he was investigated under the EP study, which confirmed fascicular tachycardia, a rare and uncommon presentation of ventricular tachycardia. The patient was successfully treated with radiofrequency catheter ablation therapy, which is curative in over 80% of the cases. This case highlights the importance of referring patients with repeatedly presenting arrhythmic episodes to undergo EP study. This will avoid putting them at unnecessary future risk, while offering the opportunity to definitely diagnose and provide curative therapy.